DNA methylation changes in response to active smoking exposure are associated with leukocyte telomere length among older adults - Gao, X.; Mons, U.; Y. Zhang; Breitling, L. P.; Brenner, H. (Eur J Epidemiol, 2016)
Telomere length (TL) is associated with an increased risk of aging-related diseases. As a preventable environmental hazard of morbidity and mortality, smoking has been reported to promote TL attrition by producing a variety of oxidants and free radicals. Since DNA methylation has been demonstrated to play an important role in the pathways of smoking and smoking-induced diseases, this study aimed to address whether the smoking-associated DNA methylation changes could be associated with accelerated TL shortening. We obtained DNA methylation profiles in whole blood samples by Illumina Infinium Human Methylation 450 Beadchip array in two independent subsamples of the ESTHER study and measured their relative TL by quantitative PCR. Terminal Restriction Fragment analysis was additionally performed in a subsample to obtain absolute TL in base pairs. TL measurements across panels were standardized by z-transformation. After correction for multiple testing, we successfully confirmed that seven out of 151 smoking-related CpG sites were associated with TL (FDR <0.05). A smoking index based on the seven loci showed monotonic associations with TL, cumulative smoking exposure and time after smoking cessation. In conclusion, our study supports suggestions that epigenetic alterations could play a role in smoking-associated disproportionate aging as reflected by TL. Further research is required to examine whether the identified epigenetic signatures of smoking can be of value in clinical practice to assess individual aging across the lifespan.
Keywords: Aged DNA Methylation/*physiology Female Germany Humans *Leukocytes Male Middle Aged Polymerase Chain Reaction Smoking/*physiopathology Telomere Telomere Shortening/*physiology *Aging *Epigenetic epidemiology *Gerontology *Smoking methylation *Telomere len